The development of Zirconia and Copper toughened Alumina ceramic insert - Nur Amalina, Sabuan; Nurfatini, Zolkafli; Mebrahitom, A.; Azmir, Azhari; Othman, Mamat (IOP Publishing, 2018)
Ceramic cutting tools have been utilized in industry for over a century for its productivity and efficiency in machine tools and cutting tool material. However, due to the brittleness property the application has been limited. In order to manufacture high strength ceramic cutting tools, there is a need for suitable reinforcement to improve its toughness. In this case, copper (Cu) and zirconia (ZrO2) powders were added to investigate the hardness and physical properties of the developed composite insert. A uniaxial pre-forming process of the mix powder was done prior to densification by sintering at 1000 and 1300°C. The effect of the composition of the reinforcement on the hardness, density, shrinkage and microstructure of the inserts was investigated. It was found that an optimum density of 3.26 % and hardness 1385HV was obtained for composite of 10wt % zirconia and 10wt% copper at temperature 1000 °C.